2014
DOI: 10.7869/tg.188
|View full text |Cite
|
Sign up to set email alerts
|

Biliary sphincteroplasty facilitates retrieval of proximally migrated plastic biliary stent

Abstract: Background and aim: Proximal migration of biliary stents presents a technical challenge for the therapeutic endoscopist. It may require multiple, complicated corrective procedures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Shah DH et al, found that balloon biliary sphincteroplasty with controlled radial expansion balloon dilator increases the retrieval rate of proximally migrated biliary stents. 8…”
Section: Discussionmentioning
confidence: 99%
“…Shah DH et al, found that balloon biliary sphincteroplasty with controlled radial expansion balloon dilator increases the retrieval rate of proximally migrated biliary stents. 8…”
Section: Discussionmentioning
confidence: 99%